Within‐subject haemoglobin variation in elite athletes: a longitudinal investigation of 13 887 haemoglobin concentration readings. Issue 2 (19th May 2015) - Lobigs, Louisa M.; Knight, Emma J.; Schumacher, Yorck Olaf; Gore, Christopher J.
Abstract : The Athlete Biological Passport (ABP) estimates individualized reference ranges for key blood markers, such as haemoglobin concentration ([Hb]), using predetermined population mean, between‐ and within‐subject variances. Here, we aim to reassess previously published estimates for within‐subject [Hb] variance and determine whether sex‐, analyzer‐, sport‐, or season‐specific values are required. Our reference population contains 7723 male (mean ± SD, 22.3 ± 4.6 years of age) and 6164 female (21.6 ± 4.3) athlete observations from 49 sports. [Hb] was calculated using one of three cytometers; Bayer‐H3 (1997–1999, n = 4554), ADVIA‐120 (1999–2010, n = 8636) and Sysmex XT‐2000i (2010–2012, n = 697). The final model was a linear mixed model for [ Hb ] with analyzer (H3, ADVIA, Sysmex), sex (male, female), sport (power‐endurance, endurance, skill, team, disabled and non‐athletes), season (summer, winter), and the interaction between sex and sport as fixed effects and athlete as a random effect. The model included an exponential correlation structure to allow for within‐subject autocorrelation, and allowed different within‐subject variances for each sport . Within‐subject [Hb] variance (g 2 /L 2 ) was significantly less for power endurance (35.09, 95% CI 33.50 to 36.76), disabled (25.82, 95% CI 21.71 to 35.28) and non‐athletes (34.30, 95% CI 28.53 to 35.87) than for endurance (40.35, 95% CI 39.62 to 47.22) and team sports (38.70, 95% CI 37.68 to 39.76) athletes. No new evidence was found to justify adjusting the current within‐subject [Hb] variance estimate. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The current value for within‐subject haemoglobin concentration ([Hb]) variation, an estimation used within the Athlete Biological Passport, was validated from an athlete database containing over 13 000 [Hb] observations. Subsequent investigations were made to quantify the proportion of within‐athlete [Hb] variance that is analytical in origin, and identify whether sex‐, analyser‐, sport‐, or season‐specific variance values are required within the key anti‐doping system that is the Athlete Biological Passport.